The Mode of Storytelling in Tere Liye's Novel Tanah Para Bandit (A Conceptual Review of Gerard Genette's Narratology) - Gobel, Savitri Wulandari; Didipu, Herman; Zulkipli, Zulkipli (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2024)
The aspect of storytelling or storytelling elements has a very important role in the structure of a novel. Storytelling is the central element in a novel that has the ability to hook the reader's interest. In fact, it can be considered that the existence of a novel becomes unimaginable without the presence of narrative elements. With the elements of storytelling present, the novel becomes more dynamic and alive in the reading experience. By analysing this aspect, researchers can understand how the components of the story are interconnected and contribute to the overall reading experience. This research raises the issue of how the mode of storytelling in the novel Tanah Para Bandit by Tere Liye. The purpose of this study is to describe the mode of storytelling in Tere Liye's Tanah Para Bandit. This research applies Gérard Genette's narratology theory with qualitative descriptive method. The research data source comes from the novel Tanah Para Bandit by Tere Liye. Data collection techniques were conducted through reading and note-taking methods. Data analysis refers to Gérard Genette's narratology theory, which includes two stages: partial analysis and integral analysis. The results show that there is a mode of storytelling with the position of the narrator as a character in the story; internally, the narrator acts as the main character who tells the story. The focalisation technique used is internal focalisation, where the narrator only conveys information known by the characters.